PENGARUH KOMBINASI ZAT PENGATUR TUMBUH Benzyl Amino Purine DAN Naphtalene Acetic Acid TERHADAP PERTUMBUHAN SUBKULTUR KENTANG (Solanum tuberosum L.) VARIETAS GRANOLA DENGAN METODE IN VITRO - Karya; Endang Kantikowati; Joko Santoso; Regina Sofia Fahma (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2025)
The study aims to determine the effect of the combination of Benziyl Amino Purine (BAP) and Naphtalene Acetic Acid (NAA) on the growth of Potato Subculture (Solanum tuberosum L.) Granola Variety Using the In Vitro Method, so that good potato seeds are obtained. This research was conducted at the Potato Seed Center (BBK) Laboratory, Sukamanah Village, Pangalengan District, Bandung Regency. West Java Province. This study used an experimental method with a Completely Randomized Design (CRD) Factorial pattern, consisting of 9 treatments and 3 replications. The first factor is the concentration of Benzyl Amino Purine or BAP (B) which consists of 3 treatment levels, namely: b1 = BAP 1 mg / l b2 = BAP 1.5 mg / l b3 = BAP 2 mg / l. The second factor is the concentration of Naphthalene Acetic Acid or NAA (N) which consists of 3 treatment levels, namely: n1 = NAA 0.1 mg/l n2 = NAA 0.3 mg/l n3 = NAA 0.5 mg/l. The parameters observed were the Number of Leaves, Number of Roots, and Number of Shoots. The results showed that there was an interaction between BAP and NAA treatments on the number of roots in the b1n3 and b2n3 treatments